Functional structure inference - Serletis, Apostolos (Emerald, 2007)
The series International Symposia in Economic Theory and Econometrics publishes quality proceedings of conferences and symposia. Since all articles published in these volumes are refereed relative to the standards of the best journals, not all papers presented at the symposia are published in these proceedings volumes. Occasionally these volumes include articles that were not presented at a symposium or conference, but are of high quality and are relevant to the focus of the volume. The topics chosen for these volumes are those of particular research importance at the time of the selection of the topic.Each volume has different co-editors, chosen to have particular expertise relevant to the focus of that particular volume. Most of the chapters in this volume were delivered as papers in two sessions that William Barnett organized at a conference held in Vigo (Spain) in July 2005, sponsored by the Society for the Advancement of Economic Theory. The volume brings together fundamental new research in economics, including relevant significant innovations in microeconometrics, macroeconomics, and monetary and financial economics, thereby making substantive contributions to the literature. This book: presents original, innovative research; covers a number of issues in macroeconomics, monetary economics, and financial economics; and is part of the ISETE series.
Keywords: Economics -- Research -- Congresses.; Macroeconomics and finance -- Congresses.; Microeconomics -- Congresses.; elektronické knihy; electronic books